2014
DOI: 10.1093/jisesa/ieu026
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Differentiation in Cornops aquaticum (Orthoptera: Acrididae): Associations With Sex, Chromosome, and Geographic Conditions

Abstract: The water-hyacinth grasshopper Cornops aquaticum (Bruner) (Orthoptera: Acrididae) is native to South America and inhabits lowlands from southern Mexico to central Argentina and Uruguay. This grasshopper feeds and lays eggs on species from the genera Eichhornia and Pontederia. Particularly, Eichhornia crassipes is considered “the world’s worst water weed,” and the release of C. aquaticum was proposed as a form of biological control. Morphometric variation on the chromosomally differentiated populations from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…These patterns of ecological variation are typical examples of Bergmann or converse-Bergmann clines. The debate on whether the size of grasshoppers along altitudinal or latitudinal gradients follows Bergman’s rule is ongoing 35 36 37 38 39 . However, researchers are more interested in the relationship between morphological variation and environmental factors over a large geographic area.…”
mentioning
confidence: 99%
“…These patterns of ecological variation are typical examples of Bergmann or converse-Bergmann clines. The debate on whether the size of grasshoppers along altitudinal or latitudinal gradients follows Bergman’s rule is ongoing 35 36 37 38 39 . However, researchers are more interested in the relationship between morphological variation and environmental factors over a large geographic area.…”
mentioning
confidence: 99%
“…Moreover, a preliminary morphometric study of two polymorphic populations indicates an association between fusion 1/6 and body size (Romero et al, 2014). As one of the centric fusions is correlated with body size-related variables (Romero et al, 2014), we suggest that the increasing cline for fusion frequency in the southern populations could be the indirect result of selection for increased body size (Colombo & Remis, 2015).…”
Section: Morphometric Analysesmentioning
confidence: 64%
“…Moreover, a preliminary morphometric study of two polymorphic populations indicates an association between fusion 1/6 and body size (Romero et al, 2014). As one of the centric fusions is correlated with body size-related variables (Romero et al, 2014), we suggest that the increasing cline for fusion frequency in the southern populations could be the indirect result of selection for increased body size (Colombo & Remis, 2015). However, we did not reject the operation of other factors, such as a correlation with as yet undisclosed environmental variables or, given the geographic marginal situation of the polymorphic populations, stochastic factors.…”
Section: Morphometric Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology and size of insect wings can be used as indicators of environmental stress or environmental conditions [56,57]. We found that the differences between the wing morphology of Changbai Mountain population and the average wing morphology of A. cerana were stably concentrated in several sites.…”
Section: Discussionmentioning
confidence: 85%